Development of Biotin and Horseradish Peroxidase Labelling against Monoclonal Antibody Amyloid-β42 and Its Application on Enzyme-Linked Immunosorbent Assay - Nur Rizky Fiero; Uus Saepuloh; Huda Shalahudin Darusman; Rachmitasari Noviana (Postgraduate, University of Mataram, 2025)
Alzheimer disease is one of the causes of dementia that could make the patient lose their memories until they unable to do normal activities. It is caused by accumulation of protein in the brain called Amyloid-β42 (Aβ42), that often used as biomarker for alzheimer by enzyme-linked immunosorbent assay (ELISA). To increase the sensitivity and accuracy, capture antibodies are conjugated with labels such as Horseradish Peroxidase (HRP) and Biotin. However, the two conjugates also differ in sensitivity and specificity, therefore this research is to find which is more optimum and stable for ELISA usage. The molecular mass of the conjugated antibodies was characterized with SDS-PAGE, result shows the pre-conjugated antibody has 150 kDa bands, conjugated antibody with labels is heavier than the pre-conjugated due to the addition of each label. Conjugated antibody tested with tetramethylbenzidine (TMB), then analyzed by ELISA reader. The measurement precision decided with %CV value with results shows dillution from 10-1 to 10-4 has %CV less than 10%, while Biotin is from 10-1 to 10-5. Optimization done by determining fixed antigen with the conjugated antibody, the optimal concentration for HRP is 10-3 while biotin is at 10-4. Stability of the conjugated antibody was also determined, HRP measurement started to unstable around second month and third month, while biotin start to unstable around fourth month, this shows the biotin is more stable than the HRP.